2017
DOI: 10.1007/s10661-017-6413-5
|View full text |Cite
|
Sign up to set email alerts
|

Is the soil quality monitoring an effective tool in consumers’ protection of agricultural crops from cadmium soil contamination?—a case of the Silesia region (Poland)

Abstract: The monitoring of soil quality should be a control tool used to reduce the adverse health effects arising from exposure to toxic chemicals in soil through cultivated crop absorption. The aim of the study was to evaluate the effectiveness of the monitoring and control system of soil quality in Poland, in terms of consumer safety, for agricultural plants cultivated in areas with known serious cadmium contamination, such as Silesia Province. To achieve the objective, the contents of cadmium in soils and vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
3
2
0
Order By: Relevance
“…64,Cd 0.39,Co 4.92,Cr 18.8,Cu 26.5,Hg 0.05,Ni 11.5,Pb 63.8, Sb 1.23, Tl 0.10, Zn 283, and Se below the limit of quantification. The results obtained in the current confirmed the findings of other researchers on the PHE contents in the arable soils of southern Poland (Loska et al 2003(Loska et al , 2004Baran and Wieczorek 2015;Mazurek et al 2017;Labaz et al 2019;Baran et al 2018;Gałuszka et al 2018;Pająk et al 2018;Piekut et al 2018;Wieczorek et al 2018;Mazurek et al 2019;Waroszewski et al 2019). Nevertheless, the direct comparison of data between different studies should be made with caution due to time and methods differences.…”
Section: Discussionsupporting
confidence: 91%
“…64,Cd 0.39,Co 4.92,Cr 18.8,Cu 26.5,Hg 0.05,Ni 11.5,Pb 63.8, Sb 1.23, Tl 0.10, Zn 283, and Se below the limit of quantification. The results obtained in the current confirmed the findings of other researchers on the PHE contents in the arable soils of southern Poland (Loska et al 2003(Loska et al , 2004Baran and Wieczorek 2015;Mazurek et al 2017;Labaz et al 2019;Baran et al 2018;Gałuszka et al 2018;Pająk et al 2018;Piekut et al 2018;Wieczorek et al 2018;Mazurek et al 2019;Waroszewski et al 2019). Nevertheless, the direct comparison of data between different studies should be made with caution due to time and methods differences.…”
Section: Discussionsupporting
confidence: 91%
“…As described previously [17] in southern Poland, where investigations were conducted, soils are generally classified as cambisols, podzols, and luvisols according to the World Reference Base for Soil Resources (IUSS Working Group 2015). The measured pH values classified the investigated agricultural soil samples as neutral in the Opolskie (pH H2O range: 6.8-7.2, mean: 7.0) andŚląskie (pH H2O range: 6.8-8.3, mean: 7.0) and slightly acidic in the Małopolskie (pH H2O range: 4.8-7.9, mean: 6.50),Świętokrzyskie (pH H2O range: 5.4-7.2, mean: 6.4), and Podkarpackie (pH Our tests of the pseudototal PHE contents in agricultural soil samples confirmed the results of the research conducted previously in the Regions of SE Poland: inŚląskie [28,[50][51][52][53], of S Poland: in Małopolskie [33,[54][55][56][57][58], and of SE Poland: in Podkarpackie [59] and inŚwiętokrzyskie [60]. Our results were also comparable to those obtained within the frame of the National Environmental…”
Section: Physico-chemical Characteristics Of Soilssupporting
confidence: 84%
“…Therefore, it can be assumed that there is a very high content of toxic metals in the forest ground cover substrate of the study areas. This is confirmed by previous studies conducted by Paj ąk and Jasik (2010) in the neighborhood of the zinc smelter 'Miasteczko Śl ąskie' S.A. and Piekut et al (2018) in Tarnowskie Gory County (Miasteczko Slaskie). High concentrations of heavy metals were found in both forest soil (average concentrations: 117.43 mg Zn/kg; 2.93 mg Cd/kg; 176.64 mg Pb/kg) [37] and soil samples from arable fields (average concentrations of Cd: 9.25 mg Cd/kg) [44].…”
Section: Discussionsupporting
confidence: 89%
“…This is confirmed by previous studies conducted by Pająk and Jasik (2010) in the neighborhood of the zinc smelter ‘Miasteczko Śląskie’ S.A. and Piekut et al (2018) in Tarnowskie Gory County (Miasteczko Slaskie). High concentrations of heavy metals were found in both forest soil (average concentrations: 117.43 mg Zn/kg; 2.93 mg Cd/kg; 176.64 mg Pb/kg) [ 37 ] and soil samples from arable fields (average concentrations of Cd: 9.25 mg Cd/kg) [ 44 ]. In the study by Nitu et al (2022), it was found that the accumulation of metals in blueberries can be ranked in the following order: Zn > Cu > Pb [ 45 ].…”
Section: Discussionmentioning
confidence: 99%